(untitled) (Philippine Journal of Agricultural Economics, 2019)
There are ongoing efforts to improve the native pig industry in Asia and the Philippines. This study investigated the flow of native pigs from the raisers to the final consumers and examined public legislation that impacts on the functioning of the chain. This descriptive study utilized a cross-sectional design of data collection obtained from a total of 80 respondents from Eastern Samar and Leyte using a survey questionnaire. Data were analyzed using descriptive statistics such as frequency, percent, mean, and range. Results showed that a farmer earns a margin of Php 500 (9.59 USD) per head for 6-7 months raising at a selling price of Php 100 (1.92 USD) per kg live. Slaughtering pigs and selling the meat by kilos give a margin of Php 1,400 (26.86 USD) per head. Processors earn a margin of Php 1,700 (32.61 USD) per head from selling lechon. Traders buy native pigs from raisers at Php 100/kilogram, live weight and earn a profit of Php 94.32 (1.81 USD) per kilogram. There are no known policies of LGUs which are focused solely on native pigs raising and their products. The lack of awareness of LGUs on native pigs’ potential seems to be the reason why there are no ordinances that are supportive solely of native pig production and marketing.